IDENTIFIKASI CEMARAN DAGING TIKUS DALAM BAKSO SAPI MENGGUNAKAN PRIMER SPESIFIK GEN CYTOCHROME b DNA MITOKONDRIATIKUS DENGAN METODE REAL-TIME PCR (POLYMERASE CHAIN REACTION) - , DIAN CITRA NINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Supervision of food products in Indonesia is not going well. Cases of violation of the production of food is still a lot going on, for example, is a forgery beef meatballs using rat meat. Guarantee authenticity meatballs are absolutely necessary to ensure that the meatballs are sold in accordance with the label. Methods for detection of rat meat in the meatball that is claimed as beef meatballs need to be developed as a form of control on the outstanding meatball products. One method that can be applied is the Real-time Polymerase Chain Reaction (RTPCR). RT-PCR was applied using specific primer (CytbRglu2L and CytbRCb9H primer) amplifying Cythochrome b gene in the mitochondrial DNA of mice but not amplify cow DNA. Melting Curve Analysis (MCA) is used to view the amplicon specificity. Specific amplicons are marked by the emergence of a peak melting temperature of the MCA curve and there is no increase in the fluorescence amplification curve. To strengthen the data analysis, the sensitivity, detection limit, and the efficiency of this method are also determined. RT-PCR method incorporating CytbRCb9H and CytbRglu2L primer can specifically amplify DNA of mice in a binary mixture of beef meatballs with a sensitivity of up to 5% levels of rat meat. Amplification efficiency is obtained ini 122.90% with a detection limit of 11.2 pg mouse DNA.